The Dialectics of Altered Experience: How to Validly Construct a Phenomenologically Based Diagnosis in Psychiatry - Messas, Guilherme; Fukuda, Lívia; Fulford, K. W. M. (Frontiers in Psychiatry, 2022)
In this paper, we present how a dialectical perspective on phenomenological psychopathology, called Dialectical Phenomenology (DPh), can contribute to current needs of psychiatric diagnosis. We propose a three-stage diagnostic methodology: first- and second-person stages, and synthetic hermeneutics stage. The first two stages are divided into a pre-dialectical and a dialectical phase. The diagnostic process progresses in a trajectory of increasing complexity, in which knowledge obtained at one level is dialectically absorbed and intertwined into the next levels. Throughout the article, we offer some examples of each step. In overall, the method starts off from the patient’s own narrative, proceeds to two stages of phenomenological reduction designed to guarantee the scientific validity of the object, and concludes with a hermeneutical narrative synthesis that is dialectically composed of the patient’s and psychopathologist’s shared narratives. At the end of this process, the initial first-person narrative is transformed into a specific scientific object, a full dialectical phenomenological psychiatric diagnosis. This form of diagnosis constitutes a comprehensive alternative for an integral assessment of the complexities of human psychological alteration, bringing together both the interpretation of the suffering person and the scientific categories of psychiatry.